2015
DOI: 10.1080/09712119.2015.1129340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of supplemental vitamin E on 56-day feedlot growth performance and plasma tocopherol concentrations in calf-fed Holstein steers

Abstract: Fifty-four Holstein steer calves, divided in two weight groupings (141.2 ± 4.9 kg and 454.2 ± 7.0 kg respectively), were used in a 56-day study to evaluate the influence of supplemental vitamin E on growth performance and plasma vitamin concentrations. Steers were assigned within body weight groupings to 18 pens, 3 steers/pen. Dietary treatments consisted of a steam-flaked corn-based growing-finishing diet supplemented to provide 0, 250, or 500 IU/d of vitamin E as all racemic αtocopherol. No morbidity was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…This is in agreement with explained by Park et al and Prado et al [13,14], where a positive growth response from ruminally protected met/lys supplementation only occurred during the growth period, and no positive response was found in the finishing period. While there was also no effect on performance could be observed from the cattle treated with diet supplemented with α-tocopherol [15].…”
Section: Discussionmentioning
confidence: 80%
“…This is in agreement with explained by Park et al and Prado et al [13,14], where a positive growth response from ruminally protected met/lys supplementation only occurred during the growth period, and no positive response was found in the finishing period. While there was also no effect on performance could be observed from the cattle treated with diet supplemented with α-tocopherol [15].…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, Cano, Montano, Salinas‐Chavira, and Zinn () reported no significant difference in feedlot Holstein steer calves fed diet containing 0, 250, or 500 IU/d of vitamin E during 56 days feeding trial, whereas Mir et al () found that steers fed diet containing 500 IU/d of vitamin E had lowered live weight and average daily weight gained compared with the control group. Similarly, Plascencia, Montano‐Gomez, Salinas‐Chavira, Torrentera‐Olivera, and Zinn () in their study found that Holstein steers fed diet containing vitamin E level at 0, 250, and 500 IU had no significant difference in the average daily weight gain, dry matter intake, gain efficiency, and carcass characteristics after 312‐day feeding trials.…”
Section: Application and Roles Of Vitamin E In Livestockmentioning
confidence: 96%
“…The discrepancies in growth performance response of livestock supplemented with vitamin E from different studies may be attributed to the effect of age and breeds, other dietary ingredients, animal stress, or supplementation period of the different trials (Cano et al, 2015;Decker et al, 2000).…”
Section: Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…While, vitamin E supplementation alone in calf-fed Holstein steers was not expected to enhance their feed lot growth performance due to health status may be a factor in short-term responses to vitamin E supplementation (Cano et al, 2017). However, our trial study lasted up to 90 days and this period may enough for showed response effectiveness.…”
Section: Discussionmentioning
confidence: 90%